Evaluation of Some Physical Properties of Soils as Factors Influencing Movement of Contaminants through Porous Soils Media of Gwari market Dumpsites, Yola, Nigeria - Burmamu, B.R.; Law, P.L. (IRJET, 2015)
Pollution is a bad thing, no matter how you look at it. We can smell it when the air gets polluted and taste it when the water has gone bad, but soil is also another element that may be susceptible to different types of pollution. The present study evaluated some physical properties of soils such as bulk density, moisture content, particles size distribution, and textural classification as parameters that affect transport of pollutants through soils of the research area. Field in-situ and laboratory studies were conducted to characterize these properties using scientific calibrated equipment. Major results showed that bulk density was 3.1215kg/cm2 at mean moisture content of 22.5% and temperature of 38.6ºC. There was correlation coefficient of 0.26 between bulk density and distance of points taken. Permeability rate was found to be 1.55cm/min and strength of relationship between points X and Y (0.9776) was positively strong while Bouyoucos hydrometer analysis produced sandy loam as textural classification of the site. This implies that the research area has low resistance to the flow of contaminants and therefore susceptible to pollution. It was recommended that before sitting any human activity/facility on an environment, there should be proper assessment of the physical properties of soils of that area.